2022
DOI: 10.3389/fpsyg.2022.888977
|View full text |Cite
|
Sign up to set email alerts
|

The implications of inefficient markets for executive pay comparison: The case of China and Poland

Abstract: Although there is a large volume of literature on executive compensation, few of these studies have focused on executive pay comparisons and even fewer on the antecedents of executive pay comparisons. This paper fills this gap in executive pay comparison literature by beginning with executive pay comparison behaviors, and then the elements that influence executive pay comparison behaviors are discussed. A questionnaire survey found that executive pay comparison behaviors exist in both China and Poland. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Annual Distribution: Figure 5 shows the tendency of Scopus-indexed articles that focused on the impact of executive compensation gap on corporate in the past ten years, from which it can be seen that before 2020, researchers paid little attention to this topic, and in 2019, there was not a single relevant study, however, since 2020, researchers began to pay more attention to this filed, and the total number of articles published in 2020-2022 reached 16, accounting for 59% of the total number of articles published in the past decade, with the largest number of articles published in 2020 and 2022, which is 7 and 6 respectively. However, in general, the attention to this research area is still insufficient, and after screening the literature that does not fit the research topic, the total number of articles in the past ten years is only 27, which coincides with the view of some researchers that current academia is still inadequate on the impact of executive compensation gap on the company (Liu and Liu, 2022;Yang, 2017). Distribution of Authors: In addition, researchers also suggest that when discussing the impact of the executive compensation gap on corporate, because of the cultural and national background differences of the researcher, the results may also differ depending on the region where the research is based.…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…Annual Distribution: Figure 5 shows the tendency of Scopus-indexed articles that focused on the impact of executive compensation gap on corporate in the past ten years, from which it can be seen that before 2020, researchers paid little attention to this topic, and in 2019, there was not a single relevant study, however, since 2020, researchers began to pay more attention to this filed, and the total number of articles published in 2020-2022 reached 16, accounting for 59% of the total number of articles published in the past decade, with the largest number of articles published in 2020 and 2022, which is 7 and 6 respectively. However, in general, the attention to this research area is still insufficient, and after screening the literature that does not fit the research topic, the total number of articles in the past ten years is only 27, which coincides with the view of some researchers that current academia is still inadequate on the impact of executive compensation gap on the company (Liu and Liu, 2022;Yang, 2017). Distribution of Authors: In addition, researchers also suggest that when discussing the impact of the executive compensation gap on corporate, because of the cultural and national background differences of the researcher, the results may also differ depending on the region where the research is based.…”
Section: Methodsmentioning
confidence: 87%
“…According to researchers, in recent years there has been a particularly high level of social and theoretical attention to the topic in the field of executive compensation (e.g. Liu and Liu, 2022;Sánchez-Marín et al, 2022). The generation of such phenomenon can be traced back to the financial crisis that happened in 2008, where it was found that, despite the negative impact of the financial crisis on the business performance of many companies around the world, many of these executives, especially chief executive officers (CEOs), still enjoy high salaries under such crisis (Sánchez-Marín et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation